Genome instability triggered by the V(D)J recombination by-product. (4th July 2019) - Kirkham, Christopher M.; Boyes, Joan
ABSTRACT: A newly identified process by which mistargeted V(D)J recombination could cause genome instability in childhood leukemia has been discovered. In this mechanism, called cut-and-run, the excised DNA by-products of V(D)J recombination are re-bound by the recombinase proteins and erroneously trigger double-strand breaks at multiple locations throughout the genome. Many of these breakpoints co-localize with known chromosome alterations in acute lymphoblastic leukemia (ALL).